2019
DOI: 10.4236/mri.2019.81001
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Cytokines Involved in Acute-Phase Wound Infection with Reference to Residence Time of Patients in Hospitals

Abstract: Background: Cytokines have a major role in mediating immunity as well as inflammation. The main proinflammatory cytokines are activated after injury and implicated in healing interleukin-1 (IL-1), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). High levels of IL-6 are recorded at initial inflammatory response and start decreasing down to eight day of wounding while TNF-α level remained static and IL-1α levels showed a different pattern of change following injury and consequence of infection. Methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…During the first phase of an injury, IL-6 starts to increase, followed by TNF-α. The level of TNF-α remains in the same current during the injury process [ 15 ]. In this study, rats from the group of cases received DSS to induce colitis.…”
Section: Discussionmentioning
confidence: 99%
“…During the first phase of an injury, IL-6 starts to increase, followed by TNF-α. The level of TNF-α remains in the same current during the injury process [ 15 ]. In this study, rats from the group of cases received DSS to induce colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IL-6 and IL-10 were shown to be interesting predictor mediators for SI diagnosed from T1 to T3. As for wound infections, previous studies have shown that patients in medical assistance for SI present elevated levels of IL-6, lasting up to 5 days after intervention [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 plays an intrinsic role in the acute-phase wound response, may modulate local and systemic post-injury events by being the most persistent cytokine to mediate post-injury complications; and is robustly correlated with adverse clinical events and outcomes after mechanical trauma, burn injury, and elective surgery [55]. On wounding, elevated levels of IL-6 were detected within 24 h of bacterial infection during the initial inflammatory phase, which gradually diminished by the eighth day [65]. IL-6 was the only pro-inflammatory cytokine, the levels of which were persistently elevated post-burn injury; IL-6 levels in the serum peaked during the first few hours after injury and correlated directly with the area of the burn injury, the magnitude of the trauma, the duration of surgery, and the risk of postoperative complications [66].…”
Section: Bmentioning
confidence: 99%